MITIGATION OF WASTE TRANSPORTATION COSTS IN TAIF PROVINCE, SAUDI ARABIA - Abdullah M. Y. Alzahrani (Rudarsko-geološko-naftni Zbornik, 2022)
Municipal solid waste (MSW) management is a critical issue in the Kingdom of Saudi Arabia (KSA). Management of solid waste in crowded conditions, especially in main cities such as the Al-Taif Province. This paper deals with that case study and focuses on how to solve material handling problems by applying conventional methods and computer ability. One of the costliest operations in the civil sector is transportation for material handling. City mayors considered transportation and materials handling as a subclass of the linear programming technique, thus linear programming problems take into consideration that the main objective is to handle materials from the city centre site to the identified dumping area. There are many methods and tools used to solve the transportation problem (TP) to find out the maximum or minimum in order to reduce cost or maximize profit. The methods related to manual solutions and others used many different computer applications. Manual solutions include the northwest corner method, the minimum cost method, the row minimum cost method, the column minimum cost method, and Vogel's approximation method, and computer applications such as LINGO, Lingo, and solver function using Microsoft Excel. This case study focuses on applying the Microsoft Excel function to find the minimum cost of the transportation system in waste materials to reduce the transportation cost from the city centre to the final destination (dumping area) to be used. The results achieved with the model aided in obtaining optimal solutions and finally, the optimal solutions were checked.